The Influence of Organizational Culture and Principal’s Leadership on Teachers’ Performance - Toyib, M Saripudin; Ahyani, Nur; Widayatsih, Tri (Yayasan Sembilan Pemuda Indonesia, 2025)
This study examines the influence of organizational culture and principal’s leadership on teacher performance in state senior high schools in Cengal District. A quantitative approach was employed using questionnaires distributed to 42 teachers. Data were analyzed using simple linear regression and multiple linear regression techniques in SPSS 26. Results indicate that organizational culture significantly influences teacher performance (R² = 62.1%), while principal leadership shows a lower but significant impact (R² = 11.1%). Combined, these two variables explain 33.0% of the variance in teacher performance, suggesting that additional factors contribute to performance outcomes. These findings emphasize the need for stronger leadership development programs and school culture improvements to enhance educational effectiveness.